A simplified method for monitoring cytokines in wound fluid. Issue 1 (26th October 2022) - Burian, Ewa Anna; Enevold, Christian; Karlsmark, Tonny; Ågren, Magnus S.
Abstract: Cytokines in wound fluid are used as surrogates for wound healing in clinical research. The current methods used to collect and process wound fluid are noninvasive but not optimal. The aim of this prospective study was to evaluate a method (NovaSwab) by which wound fluid is collected by a surface swab and eluted in a physiological buffer for subsequent cytokine analysis. Wound fluid from 12 patients with leg ulcers was assessed by NovaSwab at the start (Day 0) and at the end of a 23‐h collection period of wound fluid retained by foam oblates beneath an occlusive film dressing (Day 1). GM‐CSF, IL‐1α, IL‐1β, IL‐6, IL‐8, PDGF‐AA, TNF‐α and VEGF levels were measured by multiplex and electrochemiluminescence assays. IL‐1α (2.4×), IL‐1β (2.0×) and IL‐8 (1.8×) levels increased from Day 0 to Day 1 as detected by NovaSwab, indicating local production of these polypeptides in the wounds. On Day 1, the NovaSwab method yielded higher levels of IL‐1α (4.0×), IL‐1β (2.7×) and IL‐6 (2.7×), and 35% lower levels of VEGF than those in wound fluid accumulated for 23 h in foam oblates (on average, 5 ml of wound fluid). In vitro experiments showed that the investigated cytokines in cell‐free wound fluid were recovered in a quantitative manner by the NovaSwab method . We conclude that the method presented here is a promising research tool to study the kinetics of soluble cytokines over the course of wound healing. More studies are needed to determine the interobserver variation and reproducibility of the NovaSwab method.